The extent, structure and change of German, Japanese and US American direct investment in ASEAN countries - Martin Gross (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
The paper presents the different investment volumes and patterns for the three home countries and the ASEAN hosts, and compares the respective structures with each other. The hypothesis that different trade performances of two countries are coupled with comparatively different investment structures is tested employing some measures of structural similarity. In the second part, the FDI in developing areas are contrasted with the holdings in industrialized countries. The third part deals with the industry structure of FDI in ASEAN manufacturing industries only, thus abstracting from the distorting effect of capital intensive resource oriented investment. The intra-ASEAN structure of foreign direct investment is analyzed in the following paragraph by linking sectoral and regional structures to each other. The final section summarizes the results.
Keywords: 330